Penyuluhan Pengurus Bumdes untuk Meningkatkan Kesejahteraan Masyarakat Desa Mekarmukti Kecamatan Buahdua Kabupaten Sumedang - Edi Setiawan; Amelia Lestari Fauzy (Universitas Medan Area, 2020)
At this time, the Indonesian Community's Human Resources still need to be improved. Therefore, this Community Service takes an object consisting of downloading with the subject being a member of the Bumdes Mekarmukti Buahdua District, Sumedang Regency in the hope that the Bumdes management will be effective and effective. The bumdes management's confusion about what had to be done in the Bumdes was the main difficulty in carrying out this dedication. In addition, Mekarmukti Village which was allocated by agricultural land was prepared as limited land in the management of village bumdes. One village of one product is one of the Sumedang District Government programs in order to improve the welfare of the community that starts from the village administration. Sumedang Regency will advance if it reaches its region able to maximize existing potential. Success both in terms of natural resources and social and cultural capital is a competitive advantage for Sumedang Regency to rise. The people's economy will increase to become strong, resilient and powerful if the competitiveness index is high. The paradigm of working with the community is a method used to further apply participatory principles and independence to Bumdes administrators. The results obtained from supporting the motivation of administrators in the bumdes, the opening of any mindset that can be used as material for the Bumdes effort, the collaboration between the bumdes management and village government officials with the DPMPD of Sumedang district as a Stakeholder in village coaching is getting stronger.